THE CONCEPT OF CORRUPTION SCHEMES AND WAYS OF FIGHTING IT IN UKRAINE - Kogut-Ferens, O.I.; Dyriv , R.V. (The actual problems of regional economy development, 2023)
Corruption is one of the most dangerous phenomena for society and the state. It undermines the authority of the state apparatus, discredits its activities, destroys the basic principles on which any democratic state is based, the principles of equality of citizens before the law, justice, impartiality of justice, protection of people by law enforcement structures from all kinds of illegal encroachments and arbitrariness of officials, etc. In addition, corruption causes significant economic and political damage to the state, and seriously slows down the progressive development of society. Corruption in Ukraine practically nullifies the potential effectiveness of any economic and social programs of the state, the effectiveness of management decisions. G. V. F. Hegel also noted that part of the state power, which was acquired for himself by a separate individual, is lost to the general power. Therefore, the issue of fighting corruption remains an urgent issue for all countries. Some countries have achieved significant success and were able to build a powerful anti-corruption system from independent institutions. Some, despite all efforts, occupy relatively low positions in the world rankings due to insufficient political will, and there are also countries in which this phenomenon has penetrated all the cracks of public administration and the level of corruption reaches several times higher than the national wealth indicator. The most developed anti-corruption institutions are in the Scandinavian countries, such as Denmark, Sweden, Finland and Norway, countries of Western (old) Europe. At the same time, there is a certain trend with which the more successful the fight against corruption, the more developed the economy and the richer the country's population. The country needs an intensive movement in the fight against corruption, especially during a full-scale war, because the thesis of "reforms in exchange for financial and military aid" is increasingly appearing in both national and foreign media, since successful reforms are a guarantee from the country's government, but international aid will fulfill its primary task - help the Ukrainian army expel the enemy from our lands, and not settle in the bank accounts of certain persons. Also, successful overcoming of corruption schemes is one of the factors for attracting investments for the post-war reconstruction of the country.